ANALISIS PEMELIHARAAN JALAN TRANS PAPUA DI KABUPATEN YALIMO PROVINSI PAPUA PEGUNUNGAN - Penius Lani; Petrus Bahtiar; Harmonis Rante (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
The Trans Papua road connecting the cities of Jayapura and Wamena is a significant breakthrough in Papua's Highlands region. This road opens up land transportation that used to rely solely on air routes. The purpose of this research is to examine the effects of the Trans Papua Road on the community, the field conditions that weaken and strengthen its development, and the strategies for its development and maintenance. Primary data includes community responses regarding the Trans Papua Road and its impact on regional development, obstacles in the field, favorable conditions for the development of the Trans Papua Road, and its current state. Secondary data includes media publications, academic journals, government policies, and scientific literature related to the Trans Papua Road. Data analysis is done qualitatively and descriptively. In conclusion, the roads built in the Central Highlands of Papua facilitate connectivity and access, reduce transportation costs for basic necessities, improve time efficiency, foster new economic activities such as settlements, plantations, and agriculture, and enhance services in the education and health sectors. The factors that hinder its development are unsafe conditions, dense forests and extreme topography, climate, difficulties in communication facilities, road construction through conservation areas, limited availability of construction materials, and service providers that are unable to manage their internal issues effectively. The supporting factors are the support from the central government, the acceptance of the people of Yalimo Regency towards development, and their willingness to embrace changes for the progress of the region, along with Yalimo's considerable natural potential. The development and maintenance strategy for the Trans Papua Road includes government approach strategies, road usage management strategies, and road inspection and maintenance strategies